Western Amazonia as a Hotspot of Mammalian Biodiversity Throughout the Cenozoic - Antoine, Pierre Olivier (2017)
A state-of-the-art review of the Cenozoic fossil record from Western Amazonia is provided, based on literature and new data (regarding Paleogene native ungulates). It allows summarizing the evolution and dynamics of middle Eocene–Holocene mammalian guilds, at the level of species, families, and orders. Major gaps in the Western Amazonian mammal record occur in the pre-Lutetian and early Miocene intervals, and in the Pliocene epoch. Twenty-three orders, 89 families, and 320 species are recognized in the fossil record, widely dominated by eutherians from the middle Eocene onward. Probable Allotheria (Gondwanatheria) occur only in the earliest interval, whereas Metatheria and Eutheria are conspicuous components of any assemblage. Taxonomic diversity was probably fairly constant at the ordinal level (~12–14 orders in each time slice considered) and much more variable in terms of family and species richness: if most intervals are characterized by 40–50 co-occurring species and 19–31 co-occurring families, the early Miocene period illustrates a depauperate fauna (21 species, 17 families), strongly contrasting with the late Miocene climactic guild (82 species, 38 families). Recent mammalian taxonomic diversity from Western Amazonia (12 orders, 37 families, and 286 species) is at odds with all past intervals, as it encompasses only three orders of South American origin (Didelphimorphia, Cingulata, and Pilosa) but four North American immigrant orders (Artiodactyla, Perissodactyla, Carnivora, and Lagomorpha). In terms of taxonomic diversity, recent mammalian guilds are fully dominated by small-sized taxa (Chiroptera, Rodentia, and Primates). This overview also confirms the scarcity of large mammalian flesh-eaters in ancient Neotropical mammalian assemblages. The pattern and the timing of mammalian dispersals from northern landmasses into Western Amazonia are not elucidated yet.